Development of Digitalization of The “MP Digilib” Library System for Improvement of Academic Services - Setiawan, Aditya Chandra; Haq, Mohammad Syahidul; Khamidi, Amrozi; Putri, Adinda Rahma; Iswahyuni, Dewi Laras (Universitas Negeri Malang, 2021)
Abstract: This study aims to describe the condition of the 'Taman Baca' service of the Department of Education Management before and during the covid-19 pandemic; designing online 'Taman Baca' access service that is the application